Village Social Welfare in the Village Building Program of the TVRI East Java Public Broadcasting Institution 2021-2023 - Mohammad Hasan Fauzi; Dimas Prakoso Nugroho (Jurnal Komunikasi, 2025)
Village social welfare is an organized field of activities carried out either by the village administration or the private sector which has the main objective of fulfilling basic needs, improving the quality of life of village communities, as well as increasing village independence and overcoming social problems. This study attempts to analyze how village social welfare is described in the program "Mbangun Deso" by the East Java TVRI Public Broadcasting Institute using the Krippendorff quantitative content analysis method. The results showed that of the 88 segments analyzed, village social welfare in the "Mbangun Deso" program was described by the tourism sector being the most dominant sub-indicator in activities for utilizing the potential of natural resources, economic empowerment being the dominant sub-indicator in village community empowerment activities, building facilities and Village economic infrastructure is the dominant sub-indicator in village facilities and infrastructure development activities, economic development by the local government is the dominant sub-indicator in local economic development activities. Of the 22 villages that have been covered by LPP TVRI East Java's "Mbangun Deso" program, there are 14 villages carrying out local customs/culture preservation through direct cultural practices and 2 villages through cultural education. There are 12 villages that have modernized village government by digitizing public services.